2007
DOI: 10.1111/j.1527-3458.2007.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

The Preclinical Properties of a Novel Group II Metabotropic Glutamate Receptor Agonist LY379268

Abstract: Activation of group II metabotropic glutamate (mGlu2/3) receptors reduces excessive glutamate release that is often associated with neurodegenerative and psychiatric disorders. This finding encouraged the search for potent and selective agonists as potential therapeutic agents. The search led to the discovery of LY379268 {(-)-2-oxa-4-aminobicyclo[3.1.0]hexane-4,6-dicarboxylic acid}, which is a highly potent and systemically available mGlu2/3 receptor agonist. LY379268 was effective in several animal models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 97 publications
1
90
1
Order By: Relevance
“…As such, mGlu2/3 receptors may be an efficacious target for the development of therapeutics for the treatment of addiction (Kenny and Markou, 2004;Heidbreder and Hagan, 2005). Moreover, mGlu2/3 receptor agonists are also generating interest for their potential role in treating multiple psychiatric disorders (Imre, 2007;Patil et al, 2007;Yasuhara and Chaki, 2010), such as depression and anxiety; two disorders that are often co-morbidly expressed in alcoholics (Schuckit and Hesselbrock, 1994;Hasin et al, 2005). In addition, delineating the specific role of each receptor subtype (2 and 3, separately) would be advantageous for drug development, and with the recent emergence of selective mGlu2 and mGlu3 receptor positive modulators, future work may provide some additional insight to the contributions of activity at mGlu2 or 3 receptors in modulating the discriminative stimulus effects of alcohol and reinforcement processes.…”
Section: Discussionmentioning
confidence: 99%
“…As such, mGlu2/3 receptors may be an efficacious target for the development of therapeutics for the treatment of addiction (Kenny and Markou, 2004;Heidbreder and Hagan, 2005). Moreover, mGlu2/3 receptor agonists are also generating interest for their potential role in treating multiple psychiatric disorders (Imre, 2007;Patil et al, 2007;Yasuhara and Chaki, 2010), such as depression and anxiety; two disorders that are often co-morbidly expressed in alcoholics (Schuckit and Hesselbrock, 1994;Hasin et al, 2005). In addition, delineating the specific role of each receptor subtype (2 and 3, separately) would be advantageous for drug development, and with the recent emergence of selective mGlu2 and mGlu3 receptor positive modulators, future work may provide some additional insight to the contributions of activity at mGlu2 or 3 receptors in modulating the discriminative stimulus effects of alcohol and reinforcement processes.…”
Section: Discussionmentioning
confidence: 99%
“…Because LY379268 administration (3 mg/kg) blocked both nicotine and food self-administration , indicating a lack of reinforcer selectivity at this dose and impairment of locomotor activity at higher doses (6-10 mg/ kg; Imre, 2007), we did not assess the effects of 3 mg/kg or higher doses of LY379268 beyond Experiment 1. Importantly, LY379268 (1 mg/kg) selectively attenuated nicotine, but not food, self-administration and had no effect on locomotor activity (Imre, 2007;; therefore, this dose was used in all subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we showed that LY379268, a compound effective in animal models of schizophrenia (Cartmell et al, 1999(Cartmell et al, , 2000Clark et al, 2002;Imre et al, 2006;Imre, 2007), blocked PPI impairment associated with GLT-1 upregulation. Although the present findings do not allow predictions about clinical efficacy of LY379268, it is worth noting that the better assimilated analog LY404039 ameliorates both positive and negative symptoms in schizophrenia patients (Patil et al, 2007;Harrison, 2008).…”
Section: Ly379268 Blocks Cef-induced Ppi Impairment M Bellesi and F Cmentioning
confidence: 99%
“…The selective mGluR2/3 agonist LY379268 attenuates behavioral abnormalities in animal models of schizophrenia, and its analog LY404039 is effective in a schizophrenia phase 2 clinical trial (Cartmell et al, 1999(Cartmell et al, , 2000Clark et al, 2002;Imre et al, 2006;Imre, 2007;Patil et al, 2007;Harrison, 2008). Recently, we have shown that ceftriaxone (CEF)-induced GLT-1 upregulation impairs hippocampal long-term depression (LTD) in a DHK-reversible manner by limiting activation of mGluR2/3, thus indicating that a reduced function of mGluR2/3 mediates the effects of GLT-1 upregulation (Omrani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%